Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am having trouble trying to follow a textbook example of such a problem. Using the Lagrange's Multiplier method, we could set up a set of equations like below:

$f(x,y,z)=8(xy+yz+zx)$

$g(x,y,z)=x^2+y^2+z^2-1=0, x>0, y>0, z>0$

then the lambda could be found by solving

$8(y+z,z+x,x+y)=2\lambda(x,y,z)$

suddenly, the textbook jumps right to the conclusion that

$8(x+y+z)=\lambda(x+y+z)$

$\lambda=8$

How is it derived exactly? I've tried googling and searching for answers but I had no luck finding anything. If someone could break it down step by step, it'd be greatly appreciated. Thanks.

share|improve this question
add comment

1 Answer 1

up vote 2 down vote accepted

Just before the "jump" you have three equations $$ \begin{align} 8(y+z)&=2\lambda x\\ 8(z+x)&=2\lambda y\\ 8(x+y)&=2\lambda z \end{align} $$ Add the three left hand sides and the three right hand sides and do a bit of dividing. What do you get?

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.